Women invest in their interest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
seminar entitled The economic role of women in rural and agricultural development - the promotion of income-generating activities, which was held in October 1999 in Athens, Greece